Analytical Investigations on Short-Paneled Concrete Pavements Using Finite Element Analysis - Gupta A. (My University, 2025)
This paper numerically evaluates the effect of various parameters on the design characteristics of short-paneled concrete pavement having size ranging from 0.5 m × 0.5 m to 2 m × 2 m. A parametric study has been conducted for traffic loading using both 2-D and 3-D FEM (finite element method) through ANSYS and KENSLAB. The study also includes a comparative analysis between the effect of traffic loading and traffic with temperature loading using 3-D FEM. Results indicated that 2-D FEM yielded higher values of stresses and deflections as compared to 3-D FEM, particularly for lower thickness of slab of the order of 50 mm. For higher thickness of the order of 200 mm, the values were nearly comparable. Analysis of the results further shows that increase in slab thickness from 50 to 200 mm causes considerable reduction in flexural stresses, while the reduction in deflection was moderate. The load transfer between slabs is through aggregate interlock joints. As the panel size increases from 0.5 m × 0.5 m to 2 m × 2 m for any given thickness of slab, stresses increase significantly, while the deflection reduces. It was found that variation in the effective modulus of subgrade reaction (k-value) does not have appreciable effect on variation of stresses in the slab, whereas the deflection in the slab varies significantly. Results from 3-D FEA (3-dimension finite element analysis) on short-paneled pavements indicated that wheel stresses in combination with temperature loading yields higher values of flexural stresses as compared to traffic loading alone. A panel size of 1.0–1.5 m having pavement thickness of 130–170 mm was found to be optimum for approximately all practical k-values irrespective of loading condition. The above size and thickness yields such values of maximum flexural stresses which is safe for M40 grade concrete, generally employed for pavement quality concrete. © 2021, Shiraz University.